PEMBELAJARAN PESAN KITAB KUNING MELALUI METODE SOROGAN PADA SANTRI DI PONDOKPESANTREN DAARUS SHOFWAH - hidayat, rizki maghfiroh; Luthfie, Muhammad; Agustini, bu (Universitas Djuanda Bogor, 2020)
For students learning the message of the yellow book is a process that can produce changes in the ability to read, translate, write, and actualize the contents of the yellow book contained therein. Through this context, effective and efficient delivery learning techniques must be applied to support the learning process of the yellow book. One method that can be done is through the sorogan method for learning is more effective, because it can adjust to the level of understanding of each santri. Research to find out the message of learning the message of the yellow book conducted at Daarus Shofwah Bojonggede Islamic Boarding School, Bogor Regency. The method used is quantitative descriptive. According to (Ananto, 2013) a method that only provides an overview or description of the variables of a phenomenon under study. The population of this research is the students who study at Daarus Shofwah Bojonggede Islamic Boarding School in Bogor Regency, amounting to 40 male students. The sample in this study was taken using a sampling technique of saturated 40 male students in the Islamic Boarding School. Data collection techniques in research using primary data questionnaires and interviews, secondary data using literature studies such as books and documentation. The results of the study, the message of the yellow book through the sorogan method is very good and can help students in understanding the contents of the yellow book. From reading and translating the contents of the yellow book in Arabic without harakat on students so that there are messages of learning through the sorogan method properly. Keywords : Message of the YellowBook; The Sorogan Method; students of Islam; Islamic boarding school;